Referenciação e humor em tiras do Gatão de meia-idade, de Miguel Paiva - Souza Júnior, Rivaldo Capistrano de (2012)
This work aims to investigate the process of (re) construction upon related objects (cognitive and discursive) in comic strips and determine the function of humor regarding the outbreak in this genre. From the social cognitivism perspective, in theoretical Linguistics Textual, we argue that the word-image overlapping referents are introduced, reproduced or modified not only by co-textual tracks, but also by the social cognitivism context-interactive, and that this process recategorisen referential action is an important strategy for production of humor as it brings out the unexpected, breaking with expectations enabled the reading frame of the first pictures of the strips. The data that form the corpus for this research consist of adult-themed strips, assembled and published the book Gatão de Meia-idade (1995), written by Miguel Paiva. The results showed that the referential processes are triggered not only by means of cotextual tracks, on the interrelationship between word-image, but also by the social cognitivism context, requiring active participation of the reader in the construction of senses and new references. It was also found that the relative, to be recategorisen in textual template, contribute to an outcome or unexpected situation, unleashing the humor in the strips